Handwashing Education Through Movements and Song for the Elderly: Edukasi Cuci Tangan Melalui Gerak Dan Lagu Pada Lansia - Dientyah Nur Anggina; Putri Rizki Amalia Badri (Jurnal Pengabdian Kesehatan Komunitas, 2024)
Elderly are vulnerable to disease so it is important to maintain clean and healthy living behavior by hand washing with soap (HWWS/CTPS). The low level of hand washing knowledge in the elderly causes the importance of good and correct hand washing education in the elderly. The purpose of this activity is to implement elderly awareness in the application of HWWS. The target of the community service activity is all elderly who are registered with prolanis participants at the Family Doctor Clinic FK UMM Palembang, totaling 40 people. The method of this activity was demonstration using movements and songs. The activity was begun with registration and pretest, then a demonstration of hand washing education using movements and songs together and ended with a posttest. The enthusiasm of the participants was high. The results of the service are an increase in the knowledge of the elderly, namely 54% in the good category to 71% in the good category after education. The elderly are expected to be aware and apply HWWS behavior in their daily lives. Abstrak Orang lanjut usia (lansia) rentan terkena penyakit sehingga penting menjaga perilaku hidup bersih dan sehat dengan Cuci Tangan Pakai Sabun (CTPS). Tingkat pengetahuan cuci tangan pada lansia yang rendah menyebabkan pentingnya dilakukan edukasi cuci tangan yang baik dan benar pada lansia. Tujuan dari kegiatan ini adalah untuk menerapkan kesadaran lansia dalam penerapan CTPS. Sasaran kegiatan pengabdian adalah seluruh lansia yang terdaftar pada peserta prolanis di Klinik Dokter Keluarga FK UMPalembang yang berjumlah 40 orang. Metode kegiatan ini adalah demonstrasi dengan menggunakan media gerak dan lagu. Kegiatan dimulai dengan registrasi dan pretest, kemudian dilakukan demonstrasi edukasi cuci tangan menggunakan gerak dan lagu secara bersama-sama dan diakhiri dengan posttest. Antusias peserta tinggi. Hasil pengabdian adalah terjadi peningkatan pengetahuan lansia sebelumnya yaitu 54% kategori baik menjadi 71% kategori baik setelah edukasi. Lansia diharapkan dapat menyadari dan menerapkan perilaku CTPS dalam kehidupan sehari-hari.